P208 A case of double positivity. (26th April 2021) - Khalid, Salema; Li, Jordan; Min, Steven Young
Abstract: Background/Aims   In the absence of renal or lung involvement, the investigation of small vessel vasculitis does not routinely include checking of anti-glomerular basement membrane (GBM) antibodies. We present a patient with an MPO-ANCA positive vasculitic neuropathy who later developed anti-GBM positive glomerulonephritis. We review the literature on patients who are "double-positive" for ANCA and GBM antibodies and speculate on the utility of routinely screening all vasculitis patients for GBM antibodies in the absence of manifestations of Goodpasture's syndrome. Methods   We describe a 70 year old female who presented feeling generally unwell with reduced mobility due to discomfort in her feet. Examination was unremarkable, except for reduced temperature and joint position sense in the feet. CRP was elevated and she was found to have a weakly positive MPO titre of 32. She was treated as an MPO-ANCA positive vasculitis and neuropathy with steroids and Mycophenolate Mofetil, with a good clinical and biochemical response. Fifteen months into her treatment, routine monitoring revealed an acute kidney injury with a creatinine of 459 umol/l from a baseline of 88. Anti GBM titres were requested for the first time as part of the renal screen. MPO antibody titres were only 9, but GBM antibody titres were markedly elevated (>200). Renal biopsy showed focal necrotising glomerulonephritis, in keeping with anti-GBM disease. She was treated with steroids, cyclophosphamide and plasma exchange by the renal physicians. She remains dialysis dependant. Results   In our patient, GBM antibodies were only requested once she developed relevant clinical manifestations of anti-GBM disease. This in contrast to nephrology practise, where ANCA and GBM antibodies are routinely requested simultaneously in the context of nephritis. It could be speculated that if the GBM antibody status had been detected sooner, we may have altered her management and possibly improved her disease course. Anti-GBM disease and ANCA-associated vasculitis are both rare conditions. However, co-existence of the two uncommon diseases in individual patients is well-described and more than chance occurrence. A study showed that 5% of ANCA-positive cases were also positive for anti-GBM antibodies, while one-third of anti-GBM positive samples had detectable ANCA. Multiple studies have shown that low level ANCA antibodies develop months to years before onset of anti-GBM disease, as seen in our patient as well.The dominant disease phenotype in double positive patients is anti-GBM disease rather than vasculitis. It is very rare for isolated anti-GBM disease to relapse. In contrast, half of double positive patients experience disease relapse and therefore, require long-term follow-up and maintenance immunosuppression. Conclusion   Awareness of this double positive phenomenon is important. Rheumatologists do not routinely check anti-GBM in all vasculitis. This case highlights the importance of doing so, especially in atypical presentation of vasculitis or in relapse and refractory disease. Disclosure   S. Khalid: None. J. Li: None. S. Young Min: None.